TEOFIL ZIEMBA – ADAM MICKIEWICZ’S BIOGRAPHER - Budrewicz, Tadeusz (Prace Polonistyczne, 2022)
Teofil Ziemba (1847–1900) was a middle school teacher and a university lecturer. He taught Polish language and literature in middle school; at the university he lectured in philosophy, aesthetics, and psychology. Thanks to these university courses, he developed a research method: psychological biographical studies. Its goal was to examine life experiences and their depictions in literary works. Ziemba discovered some of the hitherto unknown documents related to the life of Adam Mickiewicz and published many articles on Mickiewicz’s life and works. His research was hardly professional – Ziemba was an amateur in literary studies. He never published innovative interpretations of Mickiewicz’s works, but he contributed to the publication of a critical biography of the poet.